Evaluasi penerapan Permendagri No.19 Tahun 2016 Dalam Penatausahaan Aset Milik Daerah Pada Badan Pengelola Keuangan Daerah Kabupaten Padang Pariaman - Novita, Rara; Fathiah, Fathiah; Yusnita, Irni (LPPM Universitas Dharma Andalas, 2024)
This study aims to determine the effectiveness of the application of regionally owned asset administration in the regional financial management agency of Padang Pariaman Regency in accordance with the Permendagri No. 19 of 2016. The object of this research is the Regional Financial Management Agency of Padang Pariaman Regency. The data used are Primary Data (KIB, FIR, BI) and Secondary (Capital Expenditure Recap and other Documentation). The indicators used in this research are Bookkeeping, Inventory, and Reporting. Data collection techniques using Observation, Interview, and Documentation. The results showed that the Regional Financial Management Agency of Padang Pariaman Regency had carried out the administration in accordance with the Regulation of the Permendagri No. 19 of 2016 has not been optimal.